Enabling Open Government - Dokeniya, Anupama (2012)
Globally, increasingly vigilant and vocal civil society groups—important actors in the new multilateralism—are demanding that companies publish what they pay in revenues, aid agencies publish what they fund, and governments publish what they spend. These initiatives reflect a renewed and heightened focus on openness, transparency, and citizen participation in the discourse and practice of governance. This idea of open government stresses information sharing and participation, rather than discretion and secrecy, as foundations of good and effective governance.